The Key Determinants of Social Media Use in Teaching during the Covid-19 Outbreak: Indonesia Case - Lia Yuliana; Lantip Diat Prasojo; Wiwik Wijayanti; Widia Murni Wijaya (Universitas Jambi, Indonesia, 2020)
This study aims to provide empirical evidence on how higher education institutions (HEIs) teacher educators use SM in teaching during the Corona Virus Disease (Covid-19) outbreak. Evaluation of the factors that are the key to implementing the use of SM in education during the Covid-19 outbreak is essential. We used a survey aiming to answer the research questions of the study. The study participants are 297 faculty members from all over the Indonesian faculty of education and teacher training. The findings of the study reported that all hypotheses are significant. Facilitating Condition (FC) significantly predicts Perceived Ease of Use (PEU) and Perceived Usefulness (PU). Similarly, PEU is positively related to PU and Intention to Use (IU). PU also significantly determines IU. In addition, IU is significantly correlated with Actual Use (AU). The highest path coefficient is achieved by the relationship between the FC and PU. PEU and PU are the lowest relationship. Suggestions and recommendations are offered for the betterment of teaching and learning processes during the Covid-19 outbreak.